Analyzing a dipeptide library to identify human dipeptidyl peptidase IV inhibitor. (15th May 2015) - Lan, Vu Thi Tuyet; Ito, Keisuke; Ohno, Masumi; Motoyama, Takayasu; Ito, Sohei; Kawarasaki, Yasuaki
Highlights: The human dipeptidyl peptidase IV inhibitory effects of 337 dipeptides were analyzed. Trp-Arg showed the highest inhibitory effect among dipeptides. N-terminal amino acids of dipeptides play a dominant role in their inhibition intensities. Five novel highly inhibitory dipeptides were discovered. The dataset provided novel insight into the development of functional food for type 2 diabetes. Abstract: Human dipeptidyl peptidase IV (hDPPIV) inhibitors provide an effective strategy for the treatment of type 2 diabetes. Because certain peptides are known to act as hDPPIV inhibitors, a dataset of possible peptides with their inhibition intensities will facilitate the development of functional food for type 2 diabetes. In this study, we examined a total of 337 dipeptides with respect to their hDPPIV inhibitory effects. Amino acid residues at N-termini dominated their inhibition intensities. Particularly highly inhibitory dipeptides discovered included the following novel dipeptides: Thr-His, Asn-His, Val-Leu, Met-Leu, and Met-Met. Using our dataset, prime candidates contributing to the hDPPIV inhibitory effect of soy protein hydrolyzates were successfully identified. Possible dietary proteins potentially able to produce particularly highly hDPPIV inhibitory peptides are also discussed on the basis of the dataset.